Students and lecturers’ perception of practices and policies applied to distance learning: a case study - Meza, Serban; Ciupe, Aurelia; Campian, Cristina; Grindei, Laura (PRATICA - Revista Multimédia de Investigação em Inovação Pedagógica e Práticas de e-Learning, 2022)
Tech-enabled Education through ICT support is a key digitalization objective achieved within the Technical University of ClujNapoca, through institutional initiatives, such as: DECIDFR - Department of Continuous Education, Distance and Low Frequency Learning; eCAMPUS – Academic Exellence through the Integrated Use of Educational Technologies and Transition towards a Virtual Campus; CeSTI - TUCN’s Integrative Study and Learning Center. The current study proposes an assessment of students’ and teachers’ perception on teaching-learning activities conducted through online environments and digital tools, during a period impacted by the SARS-COVID pandemic.